Predicting employee engagement during the COVID-19 pandemic: Does employee generation matter? - Lee, C. Christopher; Acharya, Keshab; Blair, Robert; Tyrrell, Anne M. (The journal of contemporary issues in business and government, 2023)
This paper examines various factors influencing employee engagement during the COVID-19 pandemic. The paper also explores whether the degree of such influence differs among various employee generations. A voluntary survey was conducted among 534 employees using a self- administered questionnaire. The results show that the transformational leadership style has the biggest impact on employee engagement within the workplace. While work-life balance and employee autonomy significantly influence employee engagement, corporate social responsibility moderately impacts employee engagement, particularly among the younger generation. This study is among the first to examine the impact of executive-, employee-, and organizational-level factors on work engagement during the COVID-19 pandemic and to explore the role of the employee generation in this connection.